Chemosensor development using 2-acetylpyrrole thiosemicarbazone for cu2+ ion recognition in aqueous medium: experimental and theoretical studies - Baharu, Nurul Amirah; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (2018)
A sensitive and selective colorimetric of 2-acetylpyrrole thiosemicarbazone for the efficient detection of Cu2+ has been developed. The colorimetric and optical properties of a new chemosensor of 2-acetylpyrrole thiosemicarbazone were studied by the naked-eye detection and UV-VIS spectroscopy. The ligand was synthesised from thiosemicarbazone and 2-acetylpyrrole through condensation reaction. The ligand was further characterized by melting point, elemental analysis CHNS, IR, UV-visible spectroscopy, and 1H-NMR spectroscopy. The sensitivity of 2-acetylpyrrole thiosemicarbazone was done by optimizing the solvent, ratio of solvent:co-solvent and the pH buffer that was used. The selectivity test of the chemosensor was also conducted. DMSO was chosen as the best solvent with a 5:5 ratio at pH 7. All the optimization that was used has given a significant result in the detection of Cu2+ ion. The 2-acetylpyrrole thiosemicabazone chemosensor did not encounter any interference from other metal ions. The detection limit of the probe towards Cu2+ was 1.88 x 10-5 M. The interaction by the formation of the 2-acetylpyrrole-Cu complex is 1:1 stoichiometry that was calculated using Job’s plot method. The sensing behavior of the chemosensor was further emphasized by computational studies. The sigma profile was calculated using COSMO-RS. Density Functional Theory (DFT) calculations, such as MEP, Fukui function and HOMO-LUMO energy gap were successfully calculated to visualize and clarify the interaction between 2-acetylpyrrole thosemicarbazone and Cu2+.